The Well-Being Index WHO-5: hedonistic foundation and practical limitations. Issue 3 (30th August 2019) - Kusier, Amalie Oxholm; Folker, Anna Paldam
Abstract : Research and policymaking on positive mental health and well-being have increased within the last decade, partly fueled by decreasing levels of well-being in the general population and among at-risk groups. However, measurement of well-being often takes place in the absence of reflection on the underlying theoretical conceptualisation of well-being. This disguises the fact that different rating scales of well-being often measure very different phenomena because rating scales are based on different philosophical assumptions, which represent radically different foundational views about the nature of well-being. The aim of this paper is to examine the philosophical foundation of the Well-Being Index WHO-5 in order to clarify the underlying normative commitments and the psychometric compromises involved in the translation of philosophical theory into practice. WHO-5 has been introduced as a rating scale that measures the affective and hedonistic dimensions of well-being. It is widely used within public health and mental health research. This paper introduces the philosophical theory of Hedonism and explores how two central assumptions that relate to hedonistic theory are reflected in the construction of WHO-5. The first concerns 'the hedonic balance', that is the relation between positive and negative emotions. The second assumption concerns 'the value of emotions', that is, how to determine the duration and intensity of emotions. At the end, Hedonism is contrasted with Life Satisfaction Theory, an alternative foundational theory of well-being, in order to clarify that the outlook of WHO-5 is more a rating system of positive affect than a cognitive judgement of overall life satisfaction. We conclude that it is important to examine the philosophical foundation of rating scales of well-being, such as WHO-5, in order to be fully able to assess the magnitude as well as the limits of their results.